Frontier Capitalism: Agrarian Expansion in Southern Chile, C. 1890–1930 - Robles-Ortiz, C (Blackwell Publishing Ltd, 2020)
This article argues that the agrarian expansion that took place in Chile s southern frontier region after the military occupation of the Mapuche territory (1862–1883) was the first phase of the development of agrarian capitalism in the region. This process was shaped by ecological conditions. In a territory covered by forests, sharecropping with tenant labourers was crucial for land clearance in the formation of the hacienda system, when landowners needed to create fields for commercial crops. As the domestic demand for agricultural products increased, mechanisation intensified, sharecropping declined, and wage labour became dominant. Frontier capitalist agriculture expanded dramatically, and consequently the region became the breadbasket of Chile. © 2019 Society for Latin American Studies